Pengaruh Penggunaan Prosthesis Transfemoral Terhadap Tingkat Kemampuan Mobilitas Pada Pasien Amputasi Transfemoral Dibalai Besar Rehabilitasi Sosial Bina Daksa (BBRSBD) Prof. Dr.Soeharso Surakarta - Sri Surini Pudjiastuti; Agus Setyo Nugroho; Luluk Fuadah (Poltekkes Kemenkes Surakarta, 2017)
Abstract : AMPnoPRO, AMPPRO, Transfemoral Prosthesis, Mobility Level. Transfemoral amputation is the amputation of the limbs that is performed between the hips and knees This amputation is a state that affects the patient's unthinking life. The loss of the limb causes disruption of lower limb function, thus indirectly disturbing its mobility. The purpose of this study was to determine the effect of Prosthesis on the level of mobility ability of transfemoral amputation patient. The Amputee Mobility Predictor (AMP) study on improving mobility of transfemoral prosthesis users using one-pretest and post-test group design studies, one group pretest-postes design including preexperiments. This study used a cross-sectional approach. In this design is done pretes to know the condition of the beginning of the subject before being treated so that researchers can know the condition of the subject studied before or after being treated which results can be compared or seen changes. Nine Subjects aged between 17-27 years, Using unilateral transfemoral prosthesis, muscle strength stump≥4, Normal joint motion scope. From wilcoxon statistic test obtained t = -2.687 with p = 0.007, because p <0,05, it can be concluded